2018
DOI: 10.1002/pola.29026
|View full text |Cite
|
Sign up to set email alerts
|

Self‐assembly behavior of amphiphilic linear‐block‐dendritic copolymers with long subchains: Dependences on dendron generation and mixing dynamics

Abstract: Block copolymers composed of acrylic acid and methyl methacrylate with three topologies of double linear blocks, poly(acrylic acid) (PAA) linear block/poly(methyl methacrylate) (PMMA) G1‐dendron and PAA linear block/PMMA G2‐dendron have been prepared by the combination of atom transfer radical polymerization and azide–alkyne click reaction. Proton nuclear magnetic resonance spectroscopy, Fourier transform infrared spectroscopy, and gel permeation chromatography have been adopted thoroughly to identify the chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…526 The resulting dendritic macromolecules or dendrimers could also be used to construct more complex BCPs (dendritic-linear structure). 527,528 An ABA-type triblock dendronpolymer conjugate was constructed from dendrons with anthracene groups at the focal point and linear PEG building blocks end-capped with masked maleimides. Similarly, using furan instead of anthracene, thermally reversible dendronized step-polymers were constructed.…”
Section: Novel Strategies For Efficient Assembly Of Dendrimers With Complex Architecturesmentioning
confidence: 99%
See 1 more Smart Citation
“…526 The resulting dendritic macromolecules or dendrimers could also be used to construct more complex BCPs (dendritic-linear structure). 527,528 An ABA-type triblock dendronpolymer conjugate was constructed from dendrons with anthracene groups at the focal point and linear PEG building blocks end-capped with masked maleimides. Similarly, using furan instead of anthracene, thermally reversible dendronized step-polymers were constructed.…”
Section: Novel Strategies For Efficient Assembly Of Dendrimers With Complex Architecturesmentioning
confidence: 99%
“…Synthetically, complex dendritic/dendrimer‐like architectures are achieved through the combination of CuAAC and ATRP in one‐pot with a shared Cu(I) catalyst 526 . The resulting dendritic macromolecules or dendrimers could also be used to construct more complex BCPs (dendritic‐linear structure) 527,528 . An ABA‐type triblock dendron–polymer conjugate was constructed from dendrons with anthracene groups at the focal point and linear PEG building blocks end‐capped with masked maleimides.…”
Section: Chain Propagation Via Click Chemistry (Step Growth From Monomer)mentioning
confidence: 99%
“…SAXS, cryogenic TEM and AFM were employed to investigate the structure of synthesized PEÀ S, revealing wormlike core-shell nanoparticles. [41] Li [42] et al reported caterpillar-like micelles via selfassembly of amphiphilic linear-block-dendritic copolymers, synthesizing three block copolymers containing acrylic acid and methyl methacrylate. These polymers contained three topologies such as double linear blocks, poly(acrylic acid) (PAA) linear block/poly(methyl methacrylate) (PMMA) G1dendron and PAA linear block/PMMA G2-dendron, which were characterized by NMR, FTIR and gel permeation chromatography techniques.…”
Section: Hierarchically Self-assembled Caterpillar-like Superstructuresmentioning
confidence: 99%
“…Li [42] et al . reported caterpillar‐like micelles via self‐assembly of amphiphilic linear‐block‐dendritic copolymers, synthesizing three block copolymers containing acrylic acid and methyl methacrylate.…”
Section: Introductionmentioning
confidence: 99%